PO.6.140 Treatment pattern of patients with systemic lupus erythematosus: a cohort study at rheumatologist practices in germany. (27th September 2022) - Montonen, J; De Souza, S; Foch, C; Vazquez-Mateo, C; Roy, S; Dörner, T
Abstract : Purpose: Patients with lupus are chronically exposed to anti-inflammatory and immunosuppressive treatments that are associated with considerable morbidities. This study aimed to describe treatment patterns of systemic lupus erythematosus (SLE) patients in Germany. Methods: One cohort of SLE patients who were diagnosed between 2001 and 2019 and treated at primary care rheumatologist practices were selected in the German IQVIA Disease Analyzer. This database provides anonymized data on prescriptions directly from the participating practice's computer systems. Patients were followed from the first recorded diagnosis until the earliest of their last visit or September 2020. Prescriptions were described with percentages calculated based on the number of patients with ≥1 visit during yearly time intervals. Results: A total of 423 SLE patients were included. The median (Q1, Q3) follow-up was 4.2 (1.6, 8.1) years. Median age was 50 years and 85% were female. Glucocorticoids (GCs) were the most prescribed treatments in the first 5 years following diagnosis with SLE (52–70% of patients prescribed oral GCs per year). Antimalarials and immunosuppressants were the second most prescribed treatments: antimalarials (32–39%), azathioprine (15–17%), methotrexate oral (7–10%) or subcutaneous (4–7%), and mycophenolate (5–7%). Biologics (e.g., belimumab, rituximab, tocilizumab) were prescribed for <4% of patients. Opioids were prescribed for 5–8% of patients. A trend towards decreased use of GCs was observed in SLE patients diagnosed between 2015 and 2019 versus patients diagnosed between 2001 and 2009 (47–64% vs 44–74%). Use of opioids also decreased (2–5% vs 6–13%). Biologics use remained limited (3–4% vs 0–5%). Conclusions: In primary care rheumatologist practices in Germany, GCs remain the cornerstone treatment for SLE although there is a trend of decreased usage, antimalarials are also widely used, as well as immunosuppressants. Biologic treatments are used infrequently. Pain management included use of opioids. The prescription patterns were similar to those observed in other German cohort studies (Albrecht et al. Lupus Sci Med. 2014;1 :e000059 and 2021;8 :e000526).